Pengaruh Kondisi Fisik Rumah dengan Kejadian Penderita Tuberkulosis (TB) Paru - Asrijun, Asrijun (UNM Environmental Journals, 2018)
Pulmonary TB patients in Indonesia are ranked fourth in the world after India, China, South Africa with a prevalence of 285 TB per 100,000 population or as many as 302,861 cases in 2010(Lienhardt dkk. 2012).This research is analytic observation, with case control design. Case control studies were conducted by identifying case groups and control groups. This study aims to determine the risk of physical condition of the house with the incidence of pulmonary TB in the working area of Pattingalloang Health Center, Makassar City. After conducting research, it can be concluded that; (1) There is the influence of the stage house fikik condition with the incidence of pulmonary TB with the risk of transmission 10 times from a healthy stage house. (2) There is an influence of fiksik conditions in semi-permanent homes with the incidence of pulmonary TB but not a significant risk factor. (3) There is an influence of the condition of permanent home fiksik conditions with the incidence of pulmonary TB with risk factors for transmission 6 times from a healthy permanent home..